Low temperature laser-induced fluorescence studies of chromophores in soft solids and biological matter - Lin, Chen (Kansas State University, 2013)
Low-temperature laser-induced fluorescence spectroscopy has various applications in analytical, physical, and biophysical chemistry. This technique provides information on the fluorescence origin band, zero-phonon lines and phonon-sidebands, inhomogeneous broadening, electron-phonon coupling strength, and ground- and excited-state vibrational frequencies of studied molecules. Examples discussed in this work include studies of DNA/metabolites and monoclonal antibody (mAb)/antigen interactions. The structural basis for the increased reactivity of BPDE towards guanines at 5-methylcytosine ([superscript]M[superscripte]eC):G sites in DNA was investigated by low temperature laser-based spectroscopy, studying the nature of physical complexes of benzo[a]pyrene tetraol in a series of 5-methylcytosine structural DNA analogs. We found that the presence of a C-5 substituent on cytosine and related structural modifications influences the conformation of BPT in DNA analogs, and could explain the increase in guanine reactivity at [superscript]M[superscript]eC:G sites of the p53 tumor suppressor gene that contains endogenenous 5-([superscript]M[superscript]eC. It has been demonstrated that various mAbs can bind a particular cross-reactant by adopting two distinct "red" and "blue" conformations of its binding sites. We showed that the blue conformation of pyrene in several mAbs (including 4D5 mAb) is consistent with [pi]-cation interactions, underscoring the importance of [pi]-cation interaction in ligand binding. We propose that considerable narrowing of the fluorescence origin band of the ligand in the protein environment could be regarded as a simple indicator of [pi]-cation interactions. It is also shown that time-resolved delta fluorescence line-narrowing ([delta]FLN) spectroscopy, using excitation within the (0,0)-transition band, provides more reliable information of the frequency dependence of the electron-phonon coupling (Huang-Rhys factor, (S < 1). Finally, analytical formulas were developed to describe FLN spectra with excitation energy transfer present. Our calculated FLN spectra are compared with spectra obtained by a simple convolution method (SC) and a more rigorous treatment using Redfield theory. We demonstrate that, under the condition of weak coupling between pigments (i.e., the coupling constant is smaller than the reorganization energy) and weak electron-phonon coupling strength (S < 1), our analytical formulas provide an excellent approximation of the SC and Redfield methodologies. We argued that our approach could also model FLN spectra obtained for very complex biological systems.
Keywords: Laser induced fluorescence; Fluorescence line-narrowing spectroscopy; Chemistry (0485)